Studying the Steps of the General Election Commission in Responding to the Recommendations of the Election Supervisory Body - Bintang Muhamad Hendri; Ahmad Ahmad (Universitas Negeri Gorontalo, 2023)
This research is to find out the GEC's steps in responding to Election Supervisory Body (ESB) recommendations of the Gorontalo Regency in the 2020 Pilkada. The method used in this research is a normative research type that uses a statutory and case study approach. The results of this study indicate that in responding to the Gorontalo ESB recommendation letter, the Regency GEC Gorontalo held a plenary meeting with the ability to conduct consultations with the Gorontalo Provincial GEC, then the Gorontalo Regency GEC asked for information from the election candidate as the reported party, then the GEC asked for information as well as consulted with experts including legal lecturers and also related officials who ultimately poured out the results of the study by making the Gorontalo Regency GEC decision Number: 658/KPU-Kab/X/2020 concerning Follow-Up of the Recommendations of the Gorontalo Regency Election Supervisory Body (ESB) Against Alleged Election Administration Violations, dated 17 October 2020 in Fo Form PATL-2 based on the provisions of Law Number 1 of 2015 and GEC Regulation Number 13 of 2014.